INTERNET AS COMMUNICATION MEDIUM FOR LOVEBIRDS BREEDERS AND ENTHUSIASTS IN JAKARTA, BOGOR, SOLO AND YOGYAKARTA - Ilona Vicenovie Oisina Situmeang (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Internet is one of the interactive media which enables one to interact with another or with a groupregardless of time and distance. Internet is used in a wide range of needs, such as a medium forcommunication, education, and social media for business. It is also used by Kicau Mania (acommunity of birds enthusiasts spread all over Indonesia) to have information exchange about theanimal and bird trade via Internet. Informants in this study are lovebird breeders in Jakarta, Bogor,Solo and Yogyakarta. Information obtained by breeders are mostly from blogs, social networks, andthe Kicau Mania tabloid. Internet is considered as the most effective medium for lovebird breeders andenthusiasts because it can be a medium for the exchange of information comprehensively bydisplaying photos and videos of birds.Keywords: Internet, Communication, lovebird brerders.